2004
DOI: 10.1007/s00425-004-1290-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of pepper germin-like protein as the novel PR-16 family of pathogenesis-related proteins isolated during the resistance response to viral and bacterial infection

Abstract: To understand the molecular defense mechanism controlling the hypersensitive response (HR) better, we examined the hot pepper plant (Capsicum annuum L. cv. Bugang), which exhibits an HR in response to infection by Tobacco mosaic virus pathotype P0 (TMV-P0). A full-length cDNA clone was isolated by differential screening of a cDNA library that was constructed with mRNA extracted from hot pepper leaves during the resistance response to TMV-P0. The predicted amino acid sequence of the cDNA clone exhibited a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 41 publications
2
37
1
2
Order By: Relevance
“…oryzae) pathogen attack at early (6 h) and late (120 h) stages of infection, and it was found that along with other genes, a GLP (AK060864) gene was downregulated in the resistant cultivar over the susceptible one (Kottapalli et al 2007). The first report regarding the involvement of GLP to virus infection was given by Park et al 2004 …”
Section: Expression and Biological Functions Of Glps In Green Vegetatmentioning
confidence: 99%
“…oryzae) pathogen attack at early (6 h) and late (120 h) stages of infection, and it was found that along with other genes, a GLP (AK060864) gene was downregulated in the resistant cultivar over the susceptible one (Kottapalli et al 2007). The first report regarding the involvement of GLP to virus infection was given by Park et al 2004 …”
Section: Expression and Biological Functions Of Glps In Green Vegetatmentioning
confidence: 99%
“…Southern and northern blot hybridizations were carried out with 32 P-labeled probes. Blots were hybridized as described previously (Park et al 2001a(Park et al , 2002(Park et al , 2004a(Park et al , 2004b CaWRKY-a::smGFP construction and transient expression PCR was performed using the gene-specific oligonucleotide primers 5¢-GGGATCCTATGATCTCTTCTTC ATCA-3¢ and 5¢-CGGATCCCAGTTAAGGAAAGAG zCT-3¢. Subsequently, the termination codon of the CaWRKY-a cDNA was removed.…”
Section: Dna and Rna Analysesmentioning
confidence: 99%
“…En nuestros análisis también se observó que genes que codifican para proteínas multifuncionales tipo germinas, incluidas en la categoría funcional de pared celular, estaban sobre-expresados. Estas proteínas participan en la remodelación de la pared celular, pero a la vez pueden actuar directamente contra los patógenos y tener un papel protector (Park et al, 2004). Distintos estudios han demostrado la activación de estas proteínas como respuesta a la infección por virus (Park et al, 2004;Cristofani-Yali et al, 2007;Gandía et al, 2007;Irian et al, 2007;Elivira et al, 2008;Gasca-González, et al, 2008) Por último, distintas categorías relacionadas con la respuesta a estrés estaban también inducidas.…”
Section: Discussionunclassified
“…Estas proteínas participan en la remodelación de la pared celular, pero a la vez pueden actuar directamente contra los patógenos y tener un papel protector (Park et al, 2004). Distintos estudios han demostrado la activación de estas proteínas como respuesta a la infección por virus (Park et al, 2004;Cristofani-Yali et al, 2007;Gandía et al, 2007;Irian et al, 2007;Elivira et al, 2008;Gasca-González, et al, 2008) Por último, distintas categorías relacionadas con la respuesta a estrés estaban también inducidas. La inducción de genes relacionados con el estrés biótico y abiótico es un denominador común de las infecciones virales (Dardick et al, 2007;Babu et al, 2008).…”
Section: Discussionunclassified